HUBUNGAN TEKNIK KOMUNIKASI TERAPEUTIK TERHADAP KECEMASAN ORANG TUA YANG ANAKNYA MENGALAMI HOSPITALISASI DI RUANG ANAK RSUD LANGSA TAHUN 2011 - Elfida, Elfida; Azwarni, Azwarni (Poltekkes Kemenkes Yogyakarta, 2013)
High anxiety experienced by parents whose children were hospitalized was associated with the trauma and pain that arise in children for a variety of procedures, often frustrating because of the lack of information about the procedures and the care of his children, did not know about hospital rules, do not like the taste of the staff or are afraid of receiving unwanted information. This study aims to determine the relationship Therapeutic Communication Techniques Anxiety Parents whose children suffered Hospitalization in Children's Hospital Langsa space in 2011. Correlative descriptive research design with cross sectional approach. The study population of parents whose children are being treated at Children's Hospital Langsa space. Sampling purposive sampling of 68 people by using the questionnaire. Data were statistically analyzed using Chi-square. The results showed that the lack of relationship communication techniques therapeutic hear, repeat, clarification. identification, humor informing, suggestions, silent, reflection and sharing perceptions with the anxiety of parents whose children are being treated, with a o value> O.O5 and the existence of a relationship therapeutic communication techniques focused and open-ended questions with the anxiety of parents whose children are being treated, with a value of p <0.05. It is recommended To Hospital Langsa in order to improve the understanding and motivation to implement communication therapeutic nurses with patients and their family members by providing training to nurses.